2022
DOI: 10.3390/antiox11112181
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Fortifying Nile Tilapia (Oreochromis niloticus) Diet with Different Strains of Microalgae on Its Performance, Fillet Quality and Disease Resistance to Aeromonas hydrophila Considering the Interplay between Antioxidant and Inflammatory Response

Abstract: The oxidative stress facing fish during intensive production brings about diseases and mortalities that negatively influence their performance. Along with that, the increased awareness of omega-3 polyunsaturated fatty acids (omega-3-PUFAs) health benefits has been triggered the introduction of alternative additives in aqua feed that cause not only modulation in fish immune response but also fortification of their fillet. In this context, the role of microalgae mix (NSS) containing Nannochloropsis oculate and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 122 publications
0
8
0
Order By: Relevance
“…In accordance, dietary fortifications with liposomal encapsulated TQ elevated the levels of T-AOC, CAT antioxidant enzyme and decreased the level of MDA in rabbits ( 68 ). Furthermore, dietary inclusion of microalgae mixture increased the activities of T-AOC and GPX, CAT and SOD antioxidant enzymes and decreased the level of MDA in fish, which enhanced the cells’ resistance to oxidative stress ( 69 ). Numerous studies have stated that TQ has antioxidant properties, which are responsible for eliminating free radicals and provide a significant improvement to oxidative stress responses ( 19 , 70 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, dietary fortifications with liposomal encapsulated TQ elevated the levels of T-AOC, CAT antioxidant enzyme and decreased the level of MDA in rabbits ( 68 ). Furthermore, dietary inclusion of microalgae mixture increased the activities of T-AOC and GPX, CAT and SOD antioxidant enzymes and decreased the level of MDA in fish, which enhanced the cells’ resistance to oxidative stress ( 69 ). Numerous studies have stated that TQ has antioxidant properties, which are responsible for eliminating free radicals and provide a significant improvement to oxidative stress responses ( 19 , 70 , 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been reported that some common and emerging bacterial strains isolated from diseased marine fish have homologies with pathogens that were originally found in human infections ( Rodriguez et al, 2016 ), such as V. parahaemolyticus ( Guin et al, 2019 ), S. agalactiae ( Kalimuddin et al, 2017 ), H. pylori ( Abdel-Moein et al, 2015 ), Aeromonas spp. ( Borella et al, 2020 ; Ibrahim et al, 2022a , b ), E. coli , Shigella spp., Salmonella spp., L. monocytogenes , Weissella spp. ( Castrejón-Nájera et al, 2018 ), Rahnella spp.…”
Section: Discussionmentioning
confidence: 99%
“…in seabreams; furthermore, the fungal pathogens Saprolegnia spp. and the parasites Trichodina , Chilodonela , Argulus , and Ergasilus , as well as Leeches have been known for a long time ( Kim et al, 2017 ; Buján et al, 2018 ; Duman et al, 2021 ; Abd El-Hack et al, 2022 ; Shahin et al, 2022 ; Ibrahim et al, 2022a , b ). However, many unknown or emerging etiological diseases still appear frequently in aquatic farms, seriously affecting the development of aquaculture ( Shahin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that dietary S. platensis can be recommended to counteract the oxidation induced by sodium sulphate toxicity in fish species. A 12-week feeding Nile tilapia with microalgae mixture (Nannochloropsis oculate, Schizochytrium and Spirulina species) at 0.75%, 1.5%, and 3% exhibited a higher antioxidant capacity and reduced ROS, H2O2, and MDA levels especially at 3% inclusion [88], Meanwhile, contents of EPA and DHA in tilapia fillet were significantly enhanced with an increase in NSS (microalgae mix (NSS) containing Nannochloropsis oculate and Schizochytrium and Spirulina species) levels. Such antioxidant activity could be in part due to the availability of tocopherols, phenolic compounds, and carotenoids that can reduce the oxidative stress responses in different fish species [88].…”
Section: Effects Of Microalgae On Fish Fillet Biochemical and Microbi...mentioning
confidence: 99%